2022
DOI: 10.22603/ssrr.2021-0269
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception and Geriatric Low Back Pain

Abstract: Proprioception is a deep sensation that perceives the position of each part of the body, state of movement and muscle contraction, and resistance and mass applied to the body. Proprioceptive feedback influences movement and positional accuracy, resulting in key somatosensory functions for human postural control. Proprioception encompasses signals received from proprioceptors located in the skin, subcutaneous tissue, muscles, tendons, and joint capsules, commonly known as mechanoreceptors. The muscle spindle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Significantly higher PJRS on RE of 15° and 35° were found in the CLBP group, demonstrating diminished lumbar proprioception in the CLBP group compared with the HC group, which was consistent with our previous study ( Cheng et al, 2023 ). In fact, many studies have found the poor lumbar proprioception in the CLBP group ( Brumagne et al, 2000 ; Sakai et al, 2022 ; Sheeran et al, 2012 ), which may be due to the altered paraspinal muscle spindle afference and central processing ( Brumagne et al, 2000 ). On the other hand, no differences in the repositioning tests between CLBP patients and healthy subjects was also found ( Åsell et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Significantly higher PJRS on RE of 15° and 35° were found in the CLBP group, demonstrating diminished lumbar proprioception in the CLBP group compared with the HC group, which was consistent with our previous study ( Cheng et al, 2023 ). In fact, many studies have found the poor lumbar proprioception in the CLBP group ( Brumagne et al, 2000 ; Sakai et al, 2022 ; Sheeran et al, 2012 ), which may be due to the altered paraspinal muscle spindle afference and central processing ( Brumagne et al, 2000 ). On the other hand, no differences in the repositioning tests between CLBP patients and healthy subjects was also found ( Åsell et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the proprioception should be considered for the assessment of the patients with chronic low back pain. Thus, lumbar proprioception is impaired in patients with CLBP, the differences in lumbar proprioception may not be clinically meaningful ( Korakakis et al, 2021 ), so accurate assessment of proprioception at multiple joints in lower limbs and trunk is necessary and important for establishing a precise treatment procedure ( Sakai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings of a significant negative correlation between age and performance of YBT and OLS are consistent with previous research ( 22 , 23 ). Postural balance deteriorates with age possibly caused by biological changes (e.g., neuromusculoskeletal alterations, mobility issues, and sensory-motor deficits) ( 22 , 28 ). Particularly, impaired postural balance increases the risk of falls in older CLBP patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%